More Work to Do? : Taking Stock of Latin American Labor Markets - David, Antonio (IMF Working Papers; Working Paper ;, 2019)
We analyze the performance of labor markets in Latin America since the late 1990s. Strong GDP growth during the commodity boom period led to important gains in employment and a fall in the unemployment rate as labor demand outpaced an increasing labor supply. We emphasize the role of informality in the dynamics of labor markets in Latin America. A re-examination of Okun's law shows that informality dampens changes in unemployment accompanying output fluctuations. Moreover, we present some evidence that countries with higher redundancy costs and cumbersome dismissal regulations, exhibit 'excess' informality over and above what would be expected based on their income and educational levels. Labor market reforms could thus contribute to reducing informality and increasing the responsiveness of labor markets to output growth. However, looking at selected case studies of reforms using the synthetic control method, we find mixed results in terms of labor market outcomes.